Microorganisms in Sustainable Agriculture and Biotechnology 2011
DOI: 10.1007/978-94-007-2214-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Plant Growth Promoting Rhizomicroorganisms for Enhanced Crop Productivity

Abstract: The increasing pressure on land resources has made it imperative for vertical growth through enhanced crop intensity and productivity. To meet this challenge, appropriate integrated nutrient and pest management packages must be confi gured for different agro-ecological conditions. By 2050, the crop nitrogen demand is expected to reach 40-45 million tonnes. To meet such enormous nitrogen requirements through chemical fertilizers, would not only be expensive but also could severely degrade soil health. Similar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For instance, Treating plants with PGPB has been reported to: 1) induce favorable alterations in root growth and architecture (longer roots, longer and denser lateral roots and higher biomasses) (Naseem and Bano, 2014;Timmusk et al, 2014); 2) improve shoot growth (higher shoots and heavier biomasses) (Kasim et al, 2013;Grover et al, 2014); 3) maintain relatively higher relative water contents than the drought-stressed and bacterially-untreated plants (Sandhya et al, 2010;Naveed et al, 2014;Naseem and Bano, 2014); 4) facilitate water and nutrient (e.g. Fe, P and N) acquisition (Desai et al, 2012;Ngumbi and Kloepper, 2016); 5) modulate the plant hormones levels either by synthesizing phytohormones or by lowering the plant-produced ethylene via the ACC-deaminase activity (Castillo et al, 2013;Bresson et al, 2013;Ngumbi and Kloepper, 2016); 6) stabilize membranes (Gusain et al, 2015); and 7) regulate each of expression of some drought-triggered genes (Kasim et al, 2013;Sarma and Saikia, 2014), production of osmolytes (Bano et al, 2013;Gururani et al, 2013), and activities of different enzymes (Kohler et al, 2008) resulting in promoted plant growth and productivity under drought stress (Vurukonda et al, 2016;Forni et al, 2017). Moreover, inoculating the salt-stressed barely with A. brasilense NO40 significantly ameliorated the adverse effect of salinity on growth and yield (Omar et al, 2009), but no available studies illustrating the role of S. maltophila in augmenting crop yields under abiotic stressed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Treating plants with PGPB has been reported to: 1) induce favorable alterations in root growth and architecture (longer roots, longer and denser lateral roots and higher biomasses) (Naseem and Bano, 2014;Timmusk et al, 2014); 2) improve shoot growth (higher shoots and heavier biomasses) (Kasim et al, 2013;Grover et al, 2014); 3) maintain relatively higher relative water contents than the drought-stressed and bacterially-untreated plants (Sandhya et al, 2010;Naveed et al, 2014;Naseem and Bano, 2014); 4) facilitate water and nutrient (e.g. Fe, P and N) acquisition (Desai et al, 2012;Ngumbi and Kloepper, 2016); 5) modulate the plant hormones levels either by synthesizing phytohormones or by lowering the plant-produced ethylene via the ACC-deaminase activity (Castillo et al, 2013;Bresson et al, 2013;Ngumbi and Kloepper, 2016); 6) stabilize membranes (Gusain et al, 2015); and 7) regulate each of expression of some drought-triggered genes (Kasim et al, 2013;Sarma and Saikia, 2014), production of osmolytes (Bano et al, 2013;Gururani et al, 2013), and activities of different enzymes (Kohler et al, 2008) resulting in promoted plant growth and productivity under drought stress (Vurukonda et al, 2016;Forni et al, 2017). Moreover, inoculating the salt-stressed barely with A. brasilense NO40 significantly ameliorated the adverse effect of salinity on growth and yield (Omar et al, 2009), but no available studies illustrating the role of S. maltophila in augmenting crop yields under abiotic stressed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The soil is a complex system of beneficial effects due to interactions with rhizobacteria, which depend on both the strain and the plant; the genus Bacillus, has influence on variable of plants of the type of mini-tubers and tubers. Alvarado-Capo et al, (2015), who worked with potatoes, mention that Bacillus has the advantage of forming endospores which gives great stability to act as biofertilizers or biofungicides (Desai et al, 2012) and allow them to resist adverse environmental conditions, favoring the storage of products (Moreno et al, 2018). Rhizobacteria favor root length and fresh weight and dry weight in onion plants, which coincides with the results of Angulo-Castro et al, (2018), who worked on the application and inoculation of bacterial strains in plants, demonstrating that there was greater development in plant height, leaf area, stem diameter and radical volume, they demonstrated that rhizospheric and endophytic bacteria stimulate the emergence and growth of seedlings of this species.…”
Section: Figure 2 Onion Plants In Growth Chambermentioning
confidence: 99%
“…Other mechanisms act to reduce the harmful effect of phytopathogens through the production of antagonistic substances (tetrasulfides, thiols, thiophenes and sulfur dioxide) and as producers of siderophores that sequester the iron present in the medium (Corrales-García and Ciro, 2010;Glick, 2014), as has been demonstrated, in the different mechanisms of action of a bacterial biological compound that limits the development of pathogens as indicated by the Fungicide Resistance Committee (FRAC, 2018). However, the selection of microorganisms is based on the capacity for increased production of metabolites of interest or antagonistic factor, on the use of organic substances as a source of nutrients and on the energy that allows them to survive and efficiently prevent the proliferation of phytopathogens, acting through the synthesis of antibiotics, or enzymatic biocontrol processes (Desai et al, 2012), important for agriculture especially in vegetable crops.…”
Section: Introductionmentioning
confidence: 99%